Wood ash application increases pH but does not harm the soil mesofauna. (May 2017) - Qin, Jiayi; Hovmand, Mads Frederik; Ekelund, Flemming; Rønn, Regin; Christensen, Søren; Groot, Gerard Arjen de; Mortensen, Louise Hindborg; Skov, Simon; Krogh, Paul Henning
Abstract: Application of bioash from biofuel combustion to soil supports nutrient recycling, but may have unwanted and detrimental ecotoxicological side-effects, as the ash is a complex mixture of compounds that could affect soil invertebrates directly or through changes in their food or habitat conditions. To examine this, we performed laboratory toxicity studies of the effects of wood-ash added to an agricultural soil and the organic horizon of a coniferous plantation soil with the detrivore soil collembolans Folsomia candida and Onychiurus yodai, the gamasid predaceous mite Hypoaspis aculeifer, and the enchytraeid worm Enchytraeus crypticus . We used ash concentrations spanning 0–75 g kg −1 soil. As ash increases pH we compared bioash effects with effects of calcium hydroxide, Ca(OH)2, the main liming component of ash. Only high ash concentrations above 15 g kg −1 agricultural soil or 17 t ha −1 had significant effects on the collembolans. The wood ash neither affected H. aculeifer nor E. crypticus . The estimated osmolalities of Ca(OH)2 and the wood ash were similar at the LC50 concentration level. We conclude that short-term chronic effects of wood ash differ among different soil types, and osmotic stress is the likely cause of effects while high pH and heavy metals is of minor importance. Graphical abstract: Highlights: Wood ash applied to agricultural soil had effects on collembolans at 15 g kg −1 /17.4 t ha −1 . Wood ash had no effect in organic soil. The wood ash effect is mainly due to osmotic stress. Abstract : Wood ash is not harmful to forest floor mesofauna.